Persepsi Sejarah dan Teologi Historika - Surya Harefa (STT Reformed Injili Internasional, 2022)
From the perspective of historical theology, the perception of history is an example of the importance of studying history. Narratives that are widely circulated and believed by many people do not necessarily have historical facts. Research to find and carefully examine historical facts can make one revise previously held perceptions of history. Historical theology research is no less important in the theology field than other branches of theology, such as biblical, systematics, and practical theology. From research on concepts, events, and characters in church history, Christians and the church today can understand the causes of various mistakes that have occurred in the past so that they can avoid making similar mistakes. In addition, we can also strive to develop Christian teachings and practices that are faithful to the Bible to answer the challenges of the times. Although not all of them fall into the category of historical theology, the articles in this edition are examples of efforts to explore theology and theological methods using a historical theological approach.